MODELS OF COMMUNICATION OF DA’WAH CONTENT IN THE DIGITAL ERA - Saifillah, M. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The emergence of digital technology has changed the way Dawah communication is taking place. A study on effective Dawah communication models in the digital era becomes increasingly important to understand new ways of spreading Dawah messages. This research aims to identify and analyze effective Dawah communication models in the digital era. This research used a qualitative approach with data collection techniques through interviews, observations, and literature studies. The results of the research show that effective Dawah communication models in the digital era require different strategies and tactics from conventional communication models. Some strategies found include the use of social media, multimedia content, message personalization, as well as the utilization of data and analytics to measure the effectiveness of Dawah communication. The implication of this research is that Dawah practitioners need to understand the characteristics of digital media and adjust their Dawah communication models effectively by utilizing digital technology